The Role of The Village Government in The Development of Village-Owned Enterprises (BUMDes) in Numbing Village, Bintan Regency - Nuranisyah Nuranisyah; Nazaki Nazaki; Kustiawan Kustiawan (Iustitia: Journal of Legal Theory, Politics, and International Relations, 2026)
This study examines the role of the village government in developing village-owned enterprises within Numbing Village, Bintan Regency, utilizing an empirical qualitative design based on Ryaas Rasyid's theoretical framework of governmental functions. Primary data gathered through semi-structured interviews and field observations, combined with secondary administrative documentation from 2022 to 2026, reveal that the village administration actively regulates, dynamizes, and facilitates local economic initiatives through planning documents, deliberations, capital injections, and infrastructural support. However, empirical findings indicate that enterprise development remains constrained by limited managerial capacity, low community participation, administrative bottlenecks, and unfulfilled budgetary programs such as the 2025 food security allocation. The analysis demonstrates that while statutory mechanisms provide a legal foundation for village enterprises, operational success depends heavily on continuous capacity-building programs, transparent resource allocation, and direct field mentoring. Consequently, strengthening institutional sustainability necessitates adaptive administrative leadership, enhanced human resource readiness, and collaborative networks to transform village enterprises into effective drivers of sustainable rural economic independence and community welfare